Sarthaks Test
+1 vote
531 views
in Mathematics by (128k points)

Prove that cos(π/4-x)cos(π/4-y) - sin(π/4-x)sin(π/4-y) = sin(x+y)

1 Answer

+2 votes
by (21.2k points)
selected by
 
Best answer

Solution:

cos(π/4 - x) cos(π/4 - y) - sin(π/4 - x)sin(π/4 - y)

Using formula: cosA.cosB-sinA.sinB=cos(A+B)

cos(π/4 - x) cos(π/4 - y) - sin(π/4 - x)sin(π/4 - y)
=cos{(π/4 - x)+(π/4 - y)}
=cos{π/4 - x+π/4 - y}
=cos{π/2 - x - y}
=cos{π/2 -( x + y)}
=sin( x + y)

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

Categories

...